Gram-Positive Bacterial Infections and Antibiotics Resistance in Jordan: Current Status and Future Perspective - Al-Tamimi, Mohammad; Albalawi, Hadeel; Isied, Walaa; Musallam, Ahmad; Qazzaz, Fatima; Azab, Mohammad; Abu-raideh, Jumana (Jordan Medical Journal, 2022)
Background: Antibiotic resistance is expanding worldwide at alarming rates. Middle East countries including Jordan have high prevalence of antibiotic resistance. Aims: The main aims of this review are to summarize the situation with Gram-positive bacterial infections and antibiotic resistance in Jordan, identify areas where further investigation is required, and suggest strategies to combat antibiotic resistance. Methods: A systematic literature search was conducted by two independent researchers using general and specific combinations of MeSH search terms using Embase, PubMed, Web of Science, and Google Scholar databases. Results: Staphylococci and Streptococci were commonly isolated from environmental, animal, and human samples, while Staphylococci, Enterococci, and Listeria were commonly isolated from food. Staphylococci, Streptococci, and Enterococci human colonization were documented at variable but high rates. Methicillin-resistant S. aureus (MRSA) and methicillin-resistance coagulase-negative Staphylococci (MR-CoNS) infections were common with high rates of antibiotic resistance. S. pneumoniae showed increased resistance rates to most antimicrobials. Enterococci and C. difficile resistance rates were moderate, while group B Streptococci (GBS), viridans group streptococci (VGS), C. perfringens and L. monocytogenes antibiotic susceptibility patterns were not reported. All MRSA and vancomycin-resistant Enterococci (VRE) isolates were mec-A positive, while resistance genes among CoNS, S. pneumoniae, S. pyogenes, S. agalactia, C. perfringens, and L. monocytogenes were not investigated. Conclusions: Gram-positive bacterial infections and antibiotic resistance rates were high in Jordan. Molecular epidemiology studies, a nationwide surveillance program, and action plans are urgently required to combat antibiotic resistance.